IMPLEMENTASI DIGITAL PUBLIC RELATIONS DALAM PUBLIKASI KEGIATAN PIMPINAN KOTA TANGERANG - Widyaningtyas, Mia Dwianna; Anggreyani, Fitri; Setyorini, Deviani (Telkom University, 2025)
This paper discusses digital public relations activities as a means of publication in the Protocol and Communication Section of the Tangerang City Leadership. Digital Public Relations began being used by government agencies to publicize government activities so that they are more known to the public. Implementing digital Public Relations in government agencies refers to elements in digital PR, namely transparency, internet porosity, the internet as an agent, richness in content, and reach. This study aims to determine the implementation of five digital Public Relations elements by the Tangerang City section in publishing leadership activities. The research uses a qualitative approach—data collected by interview and observation techniques. The study results show that the Protocol and Communication Section of the Tangerang City Leadership implements the element of controlled transparency by disseminating information in a controlled manner and over-transparency through the agency's social media platform itself. Research also shows that Instagram and websites are the main media in distributing publications digitally. Another finding in this research is cooperation with online media and influencers to help with the publication process. This study concludes that Digital Public Relations publicizes the activities of Tangerang City Government leaders in the form of diverse content in the form of words, images, videos, and infographics, and it uses Instagram to reach a wider audience. The significance of this research is to provide insight into the practice of digital Public Relations in Government Agencies at the Regency/City level. Keywords: Public Communication, Digital Public Relations, City Government, Publication